Cohabitation - An Increasing Phenomenon: Is it an Emerging New Norm? People’s Perspective - Mmolai, Sana Koketso; Ofhimile, Dorcus (Advances in Social Sciences Research Journal, 2014)
Traditionally, Batswana youth lived with their parents or close relatives and were to adhere to the rules and regulations of their societies. Apparently, under such conditions cohabitation was unheard of as it was shunned openly. In recent times cohabitation has been increasing yet it is neither socially respected nor legally recognized. Consequently, we aimed to investigate whether this phenomenon is being accepted as a new norm or not. In this paper we present the findings of a study conducted on perceptions of Batswana towards cohabitation. Purposive sampling was used to select 20 people from Gaborone and Tswapong region to participate in the study and interviews were employed to gather information for the study. The study revealed that though cohabitation is publicly practiced by many people, it is not yet accepted as a new norm. The study also revealed several challenges emanating from arrangements of such relationships. This paper therefore concludes that in order to encourage the spirit of accountability and respect, cohabitation could or should be discouraged among Batswana. It further recommends that cohabitation as a topic could be included in the Moral Education syllabus to enable learners to explore the moral implications of this emergent phenomenon.